Heterostructured Electrocatalysts for Hydrogen Evolution Reaction Under Alkaline Conditions - Wei, Jumeng; Zhou, Min; Long, Anchun; Xue, Yanming; Liao, Hanbin; Wei, Chao; Xu, Zhichuan J. (Nano-Micro Letters, 2018)
The hydrogen evolution reaction (HER) is a half-cell reaction in water electrolysis for producing hydrogen gas. In industrial water electrolysis, the HER is often conducted in alkaline media to achieve higher stability of the electrode materials. However, the kinetics of the HER in alkaline medium is slow relative to that in acid because of the low concentration of protons in the former. Under the latter conditions, the entire HER process will require additional effort to obtain protons by water dissociation near or on the catalyst surface. Heterostructured catalysts, with fascinating synergistic effects derived from their heterogeneous interfaces, can provide multiple functional sites for the overall reaction process. At present, the activity of the most active known heterostructured catalysts surpasses (platinum-based heterostructures) or approaches (noble-metal-free heterostructures) that of the commercial Pt/C catalyst under alkaline conditions, demonstrating an infusive potential to break through the bottlenecks. This review summarizes the most representative and recent heterostructured HER catalysts for alkaline medium. The basics and principles of the HER under alkaline conditions are first introduced, followed by a discussion of the latest advances in heterostructured catalysts with/without noble-metal-based heterostructures. Special focus is placed on approaches for enhancing the reaction rate by accelerating the Volmer step. This review aims to provide an overview of the current developments in alkaline HER catalysts, as well as the design principles for the future development of heterostructured nano- or micro-sized electrocatalysts. Highlights: 1 Heterostructured catalysts offer improved HER activities in alkaline solutions due to their fascinating synergistic effects on the heterogeneous interfaces. 2 Representative heterostructured HER catalysts for alkaline media are summarized. 3 Acceleration of the Volmer step, crucial for alkali-active catalysts, is highlighted.